Sustained accuracy improvement in intraocular lens power calculation with the application of quality control circle. Issue 1 (December 2017) - Lin, Lei; Chang, Pingjun; Xie, Jialu; Li, Zhangliang; Zhang, Hongfang; Lu, Fan; Zhao, Yun-e
Abstract Accurate intraocular lens (IOL) power calculation is always a challenge in ophthalmology, and unoptimized process may lead to inaccurate refractive outcomes. Quality control circle (QCC) has shown its success in many fields as a process management tool. However, its efficacy in ophthalmology remains unclear. Here we utilized the QCC method to optimize the process and evaluate its efficacy in improving the accuracy of IOL power calculation. After the QCC application, the percentage of eyes with achieved refractive outcomes within 0.5 diopter significantly increased from 63.2% to 80.8% calculated by Haigis formula and 59.2% to 75.8% by SRK/T formula in patients with normal axial length (AL) (22 mm ≤ AL < 26 mm). Although there were no statistically significant differences in patients with long AL by the two formulas (p = 0.886 and 0.726), we achieved an accuracy of 75% with the application of the PhacoOptics software, which was significantly higher than that using the other two formulas (p < 0.001). Our findings indicated that QCC optimized and standardized the process of IOL power calculation, thus improved the accuracy of IOL power calculation in patients who underwent cataract surgery.